Cognitive Decline in Older Patients With Non‐ST Elevation Acute Coronary Syndrome. Issue 4 (19th February 2019) - Gu, Sophie Z.; Beska, Benjamin; Chan, Danny; Neely, Dermot; Batty, Jonathan A.; Adams‐Hall, Jennifer; Mossop, Helen; Qiu, Weiliang; Kunadian, Vijay
Abstract : Background: Dementia is a growing health burden of an aging population. This study aims to evaluate the prevalence of cognitive impairment and the predictors of cognitive decline at 1 year in older patients with non‐ST–elevation acute coronary syndrome undergoing invasive care. Methods and Results: Older patients with non‐ST–elevation acute coronary syndrome were recruited into the ICON1 study. Cognition was evaluated using Montreal Cognitive Assessment. The composite major adverse cardiovascular events comprised death, myocardial infarction, unplanned revascularization, stroke, and significant bleeding at 1 year. Of 298 patients, 271 had cognitive assessment at baseline, and 211 (78%) had follow‐up Montreal Cognitive Assessment at 1 year. Mean age was 80.5±4.8 years. There was a high prevalence (n=130, 48.0%) of undiagnosed cognitive impairment (Montreal Cognitive Assessment score <26) at baseline. Cognitive impairment patients were more likely to reach major adverse cardiovascular events by Kaplan–Meier analysis ( P =0.047). Seventy‐four patients (35.1%) experienced cognitive decline (Montreal Cognitive Assessment score drop by ≥2 points) at 1 year. Recurrent myocardial infarction was independently associated with cognitive decline at 1 year (odds ratio 3.19, 95% confidence interval 1.18–8.63, P =0.02) after adjustment for age and sex. Conclusions: In older patients undergoing invasive management of non‐ST–elevation acute coronary syndrome, there is a high prevalence of undiagnosed cognitive impairment at baseline. Recurrent myocardial infarction is independently associated with cognitive decline at 1 year. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01933581. Abstract : See Editorial by Lowenstern and Wang